Evolutionary Overview of Central Banking in Nepal: An Account of Law and Practice - Kalika, Satya Narayan (Management Dynamics, 2019)
There are a number of legal and non-legal research works done in regard to analyzing the powers, functions and roles of Central Banks. However, there is the need of a study on the evolutionary aspects of central banking laws and practices. This study aims to fulfill that purpose by giving an account of the historical and evolutionary development of central banking in Nepal. It highlights both the law and practice parts of the evolution of central banking, and gives an account of the major laws and their enactments.